Alcohol-Initiated Dinitrile Cyclization in Basic Media: A Route Toward Pyrazino[1,2-a]indole-3-Amines - Festa, Alexey A.; Golantsov, Nikita E.; Storozhenko, Olga A.; Shumsky, Alexey N.; Varlamov, Alexey V.; Voskressensky, Leonid G. (Synlett, 2018)
A selective route to the formation of 1-alkoxypyrazino[1,2-a]indole-3-amines through alcohol-initiated dinitrile cyclization, starting from N-(cyanomethyl)indole-2-carbonitriles under basic conditions, was discovered. The resulting compounds were shown to be unstable in solution, and a three-component reaction of the dinitrile, alcohol, and aromatic aldehyde was used to overcome the problem.
Keywords: pyrazinoindoles; cyclization; dinitriles; domino reaction; multicomponent reaction; transition-metal free